Construction of an Infectious Clone of the Badnavirus Cacao Swollen Shoot Ghana M Virus and Infectivity by Gene Gun- and Agrobacterium-Mediated Inoculation - Keith, Cory V.; Ramos-Sobrinho, Roberto; Marelli, Jean-Philippe; Brown, Judith K. (Frontiers in Agronomy, 2021)
Cacao swollen shoot disease (CSSD) is a damaging disease of Theobroma cacao L. associated with infection by a group of poorly characterized badnaviral species. To establish causality and characterize the symptomatology associated with infection by the badnavirus cacao swollen shoot Ghana M virus (CSSGMV), an infectious clone (1.3-mer) was constructed and used to inoculated cacao “Amelonado” seedlings by biolistic inoculation (BI; n = 18) and agroinoculation (AI; n = 15). Newly expanded leaves of BI (10/18) and AI (12/15) plants developed foliar mosaic and curling symptoms 30-days post inoculation (dpi), with chlorotic mottling and necrotic crinkling being evident by 90 dpi. By 120 dpi, three of 15 AI plants exhibited characteristic stem-swelling. Viral infection was verified by PCR-amplification and sequencing of a 1068 bp fragment of the CSSGMV ORF3 from newly expanding leaves 60 dpi. The PCR results indicated that 14 of 18 and 15 of 15 BI and AI plants, respectively, were systemically infected. The complete CSSGMV genome sequence was determined, by Illumina sequencing, from representative AI and BI plants and shared >99.5% pairwise nucleotide identity with CSSGMV-Nig9 (GenBank Accession No. MH785299). Based on the development of characteristic CSSD symptoms and recovery of partial and complete genome sequences of CSSGMV-Nig9 from systemically infected cacao plants, Koch's postulates have been fulfilled.